Macular irregularities of optical coherence tomographic vertical cross sectional images in school age children - Takehiro Yamashita; Hiroto Terasaki; Ryo Asaoka; Naoya Yoshihara; Naoko Kakiuchi; Taiji Sakamoto (Scientific Reports, 2021)
Abstract The purpose of this study was to compare the incidences of macular irregularities of elementary school (ES) and junior high school (JHS) students. This was a prospective cross-sectional observational study of 122 right eyes of 122 ES students (8–9 years) and 173 right eyes of 173 JHS students (12–13 years). Vertical cross-sectional images of the macula were obtained by optical coherence tomography. The eyes were classified based on the vertical symmetry of the posterior pole, and then sub-classified as convex-, flat-, concave-, or dome-shaped based on the direction of the curvature of the retinal pigment epithelium. One hundred and two eyes (83.6%) were placed in the symmetrical group in the ES students and 149 eyes (86.1%) in the JHS students. Twenty eyes (16.4%) were placed in the asymmetric groups in the ES students and 24 eyes (13.9%) in the JHS students. In symmetrical group, 78 and 118 eyes had a convex-shape (76.4 and 79.2%), followed by 22 and 29 eyes of dome-shaped group (21.6 and 19.4%) in ES and JHS students respectively. Because the incidences of the posterior pole shapes were not significantly different between the groups, it is likely that the macular irregularities develop before the age of ES.